The manufacture and reliability analysis of the all-rigid Fabry–Perot resonator for fiber-optic acoustic sensors - Zheng, Yongqiu; Chen, Jiamin; Bai, Jiandong; Li, Zonghao; Zhao, Xinyu; Xue, Chenyang (Frontiers in Physics, 2023)
By the continuous development of aerospace, petroleum exploration, and other industrial fields, the fiber-optic acoustic sensor (FOAS) with high reliability is a desideration sensor, which can be used for noise monitoring in the extremely harsh environment. The FOAS based on the all-rigid Fabry–Perot resonator (FPR) relies on the new acoustic sensitive principle, where the change in the air refractive index is induced by sound waves and gets rid of the distortion caused by the mechanical characteristics of the acoustic sensor based on the movable parts. So, the FPR-based FOAS is very suitable for acoustic sensing in the harsh environment. In this paper, the reliability of this kind of FOASs is simulated and analyzed. The modal and anti-vibration simulation results of FPR with different sizes show that the FPR has a high natural frequency, and the external vibration environment does not affect the acoustic sensitivity of the FPR. The micro and small-batch all-rigid FPR can be manufactured by the optical contact. Moreover, the FPR can withstand the high temperature of 500°C that is verified by rapid heat treatment equipment. In order to improve the reliability of the FOAS, the metal packing shell is designed and fabricated. Moreover, the vibration and high-temperature tests of the packaged sensor are carried out. The two groups of tests show that the sensor can work normally under 10 g of acceleration vibration and 200°C high temperature, respectively. Therefore, the FOAS based on the FPR has high reliability and is very suitable for noise monitoring in the extreme harsh environment of various industrial fields. Furthermore, the research results of this paper will enhance the competitiveness and influence of the commercialized FOAS.